FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM PRODUSEN SUSU SAPI DI BOYOLALI - Lilis Mulyaningrum; Astuning Saharsini (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This research was conducted to determine the effect of using information technology, capital and length of business on the income of MSMEs producing cow's milk in Boyolali. This study applies primary data sources by distributing questionnaires and using quantitative methods. The sample for this research was taken using a purposive sampling method with a total of 35 respondents from cow's milk producers in Boyolali. This research analysis tool uses multiple regression analysis. The results of the study show that the use of information technology and capital has a significant effect on MSME income, while the length of business has no significant effect on MSME income.